Determinants of Foreign Direct Investment in GCC (Gulf Cooperation Council) Countries: Analysis of Economic Growth, Inflation, and Political Stability for the Period 2002-2018 - M Widyarta Wijaya; Wijianto Wijianto; M Fikri Himmawan (Review of Islamic Economics and Finance, 2021)
AbstractPurpose – This research investigates the factors of foreign investment inflows (PMA) that are encouraged in the member countries of the GCC (Gulf Cooperation Council).Methodology - The sample selection for observations was based on six countries, including the United Arab Emirates (UAE), Kuwait, Qatar, Oman, Bahrain, and Saudi Arabia. The data for this study were obtained from the World Bank and Asian Development Bank (ADB) database for the period 2002-2018. This study adopts panel regression analysis and uses the Random Effect Model.Findings - This research reveals that GDP and Inflation are positive and play a significant role in driving FDI inflows in GCC countries. Meanwhile, Political Stability (PSAV) does not have a substantial impact on FDI inflows in the GCC countries. This study shows that the GCC countries must provide a conducive investment environment that is represented by higher GDP growth and is involved in various international trade agreements as these factors have a higher likelihood of impacting inflows FDI. Other than that, rules describing investment priorities among members should be ratified immediately to reduce the percentage of FDI inflows out of GCC countries. Thus, this research provides significant insights for policymakers for the GCC countries to attract FDI inflows into the country.Keywords: Foreign Direct Investment, Gulf Cooperation Council Panel Regression.